25 years of research put RIPK1 in the clinic. (January 2021) - Liu, Lin; Lalaoui, Najoua
Abstract: Receptor Interacting Protein Kinase 1 (RIPK1) is a key regulator of inflammation. To warrant cell survival and appropriate immune responses, RIPK1 is post-translationally regulated by ubiquitylations, phosphorylations and caspase-8-mediated cleavage. Dysregulations of these post-translational modifications switch on the pro-death function of RIPK1 and can cause inflammatory diseases in humans. Conversely, activation of RIPK1 cytotoxicity can be advantageous for cancer treatment. Small molecules targeting RIPK1 are under development for the treatment of cancer, inflammatory and neurogenerative disorders. We will discuss the molecular mechanisms controlling the functions of RIPK1, its pathologic role in humans and the therapeutic opportunities in targeting RIPK1, specifically in the context of inflammatory diseases and cancers.